2021
DOI: 10.1002/aenm.202102025
|View full text |Cite
|
Sign up to set email alerts
|

Metal/Oxide Heterojunction Boosts Fuel Cell Cathode Reaction at Low Temperatures

Abstract: Among several types of low‐temperature solid oxide fuel cells, hydrogen‐permeable metal‐supported fuel cells (HMFCs) are devices that can achieve outputs of approximately 1.0 W cm−2 at 400 °C. This work clarifies the mechanism for promoting the cathode reaction on proton‐conducting ceramics at such low temperatures. Combined numerical and electrochemical analyses demonstrate that blocking minor oxide ion conduction at metal/oxide heterojunctions promotes proton transfer at the cathode/electrolyte interfaces, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…Assuming the linear dependence of R O on electrolyte thickness reveals the existence of an R O of about 0.7 Ω cm 2 at zero thickness. Recent studies reported that proton-conducting solid oxide fuel cells (H-SOFCs) possess large impedances (∼10 5 Hz) due to slow proton transfer at the electrolyte–anode–gas TPB. On the basis of these, the BZCY622 cells involve relatively large resistances related to the interfacial proton transfer from the electrolyte to the anode. The value estimated for the zero thickness electrolyte cell without AFL, i.e., 0.7 Ω cm 2 , is comparable to 80% of R O for the 15-μm-thick electrolyte cell without AFL (0.81 Ω cm 2 ), which confirms that the interfacial resistances are a dominant component in the R O of the BZCY622 base cells.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Assuming the linear dependence of R O on electrolyte thickness reveals the existence of an R O of about 0.7 Ω cm 2 at zero thickness. Recent studies reported that proton-conducting solid oxide fuel cells (H-SOFCs) possess large impedances (∼10 5 Hz) due to slow proton transfer at the electrolyte–anode–gas TPB. On the basis of these, the BZCY622 cells involve relatively large resistances related to the interfacial proton transfer from the electrolyte to the anode. The value estimated for the zero thickness electrolyte cell without AFL, i.e., 0.7 Ω cm 2 , is comparable to 80% of R O for the 15-μm-thick electrolyte cell without AFL (0.81 Ω cm 2 ), which confirms that the interfacial resistances are a dominant component in the R O of the BZCY622 base cells.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Jeong et al employed H 2 permeable metal-supported fuel cells (HMFCs), using Sc doped BaZrO 3Àd (BZS) electrolytes, and LSCF6428 as a cathode, to investigate the electrochemical mechanism of HMFCs. 204 Interestingly, as concluded in the literature, the proton concentration gradients and the cathode reaction at the TPBs could be harshly prompted by blocking the oxide ion conduction at the anode. Consequently, the polarization resistances of the HMFCs with LSCF6428 were decreased by a factor of 2-3.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 93%
“…[3,4] Accordingly, intensive efforts have been dedicated to pursuing novel cathode compositions with remarkable oxygen reduction reaction (ORR) activity. [5][6][7][8][9] Mixed ionic-electronic conducting perovskite-type oxides are judged as one of the potential candidates in cathode development, which considerably expand the ORR active sites from the three-phase boundary to the entire exposed electrode surface. Significant research progresses include La 0.6 Sr 0.4 CoO 3-δ , Sm 0.5 Sr 0.5 CoO 3-δ , Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF), and PrBa 0.5 -Sr 0.5 Co 1.5 Fe 0.5 O 5+δ , [10][11][12][13] all of which are based on cobalt-rich perovskite materials.…”
Section: Introductionmentioning
confidence: 99%